Penilaian kinerja sistem irigasi berdasarkan pendekatan permen PUPR No.12/PRT/M/2015 dan metode MASSCOTE di daerah irigasi Reban Batu Sumbawa Barat - Sukma, Dwi Mahenra; Hartana, Hartana; Setiawan, Ery (Universitas Muhammadiyah Mataram, 2022)
The Reban Batu irrigation area located in West Sumbawa Regency has experienced a decline in the performance of its irrigation system. Therefore, it is necessary to make efforts to improve the performance of the irrigation system by carrying out maintenance and rehabilitation, which is based on the results of the irrigation performance index assessment. The purpose of this study is to determine the irrigation system performance index in the Reban Batu irrigation area and the variables that affect irrigation performance. As for the irrigation system performance assessment, it can be based on the decree of PUPR No. 12/PRT/M/2015 and the MASSCOTE Method. The irrigation system performance assessment was carried out by direct surveys of the location and interviews with Water User Association (WUA) Farmers as beneficiaries and operational and maintenance (OM) officers as managers, resulting in a performance index based on the decree of PUPR 68.26% which was included in the category of underperforming and requiring attention. Meanwhile, based on the MASSCOTE method, the score is 2.69 or the level of service is in the poor category. Based on path analysis, the indicator variables of Irrigation Service (X1), WUA (X2), Human Resources of OM Officers (X3), and the Modernization of OM (X4)together have a significant effect on the irrigation performance variable (Y) of 0.931 or 93.1%.